EVALUATION OF PASSIVE FIRE PROTECTION SYSTEMS IN SUPERMALL BUILDINGS - N. Vinky Rahman; Elky Fernanda (Talenta Publisher, 2019)
Evaluation of a passive fire protection system is an effort to find out how feasible a fire protection system is in a building. One of the main problems arising from fire hazards in mall buildings is fire protection systems that do not meet standards. This study aims to analyze the building fire protection system, with the Sun Plaza Medan case study with a total of six floors and one basement, and located in the city center. The method used in this study is descriptive qualitative and quantitative, with a variable observation stage which is then carried out by a comparison process using the Analytical Hierarchy Process. This AHP method is helpful for researchers to get the results needed. Evaluation results obtained at shopping centers (case studies: Sun Plaza Medan) can be categorized as good, although several components do not meet the standards. Several recommendations were made for changes by testing, to obtain an increase in the value of the reliability of the passive fire protection system in the case study.